The Final Choice—Death or Transcendence? by Michael Grosso - Ginsberg, Robert (Journal of Scientific Exploration, 2018)
I remember being intrigued by the title of this book years ago, as it is a revised and updated version of an earlier work of Michael Grosso. The title seems to imply that we all have a choice as we are leaving the physical body, the option of expiring into nothingness or moving to a realm beyond the material world. I wondered why one would choose the former, and exactly who is making that choice? By the time one finishes the logical sequence of evidence, history, and theory that unfolds in the book, it becomes clear that the title’s inference is not what some might expect. Grosso believes that there are no final choices. Accepting finality is not logical when one comes to believe that our consciousness survives bodily death, and he believes that physical death is not permanent extinction, but a gateway to more living. The underlying and not so subtle message in the book has not only stood the test of time, but has become more relevant in view of today’s state of affairs. Considering the increasing threat of nuclear obliteration, climatic shifts, world divisiveness and conflict, natural disasters, pollution, famine, mass shootings, drug epidemics, and refugees roaming the planet, are these potential calamities something that could jolt the collective mind into a greater spiritual reality? The author has an interesting theory based upon near death experience research.